The influence of psychological factors on sports injuries. Review of the literature - Junge, A. (The American Journal of Sports Medicine, 2000)
The influence of psychological factors on sports injuries has been demonstrated in numerous empirical studies. Almost all investigations have been based on stress theory or a personality-profile approach. Although the majority of studies have employed different methods, the results are in general agreement that "life events" can influence the risk of injury in athletes. In this context, social support appears to have a buffering effect. According to existing results, the influence of stress-coping strategies is somewhat questionable. From the numerous psychological attributes that have been investigated in relation to sports injuries, only competitive anxiety has been shown to be associated with injury occurrence. A personality profile typical of the "injury-prone" athlete does not exist. However, several studies have shown a certain readiness to take risks (lack of caution, adventurous spirit) on the part of injured athletes. In this review, the current knowledge regarding the relationship between psychological factors and sports injuries is presented and a stress theory model is developed.